Area size mediates the role of arthropods on ecosystem functioning. (24th May 2016) - Paolucci, Lucas N.; Sobrinho, Tathiana G.; Schoereder, José H.
Abstract: Several impacts arising from anthropogenic activities hinder ecosystem properties, but the effects of habitat area size on ecosystem functioning remain little known. We aimed to evaluate the effects of area size, and the associated abundance and species richness of collembola, oribatid mites and other arthropods on litter decomposition, phosphorus and nitrogen release within tropical forests. We designed a natural mesocosm experiment with plots varying in area size (0.16 – 3.24 m 2 ), with both a control and a faunal limitation treatment (naphthalene addition). After 240 days we found lower litter decomposition and higher phosphorus release (both about 30%) in litterbags from the faunal limitation treatment. However, variations on these ecosystem properties were not related to area size, arthropod richness or abundance in this treatment, likely because of the loss of key species. Conversely, plots without faunal limitation showed a positive linear effect of area size on decomposition, and interactive effects among area size and collembolan richness, abundance and other arthropod richness. The larger the area, the smaller the positive role of collembola and other arthropod richness on decomposition, while the opposite pattern occurred for collembolan abundance. The indirect effects of arthropods on decomposition have a more significant role within smaller areas, which have a restricted microbial community with a lower array of fungal enzymes and foraging strategies available. As far as we know, this is the first evidence that the role of arthropods in decomposition may be mediated by area size, but only when arthropod biodiversity has not been reduced. We highlight the need for further assessments of these relationships in larger scales, while also measuring microbial communities, as the impact of biodiversity loss on ecosystem functioning may be even greater when coupled with habitat loss.